The Structure and Agency Role in Green Building Industry Adaptation: Malaysia’s Green Building Index Development - Ghani, Muhsin Abdul; Yusoff, Mohd Nazaruddin; Sohaimi, Nor Suzylah (CENTRAL ASIA AND THE CAUCASUS, 2024)
In modern cities, construction are the principal users of energy, accounting for 70% of total electricity consumption plus 30% to 40% of total energy consumption. As a result, the building industry offers enormous prospects for reducing energy use using energy- saving technologies. In the green building industry, this research aims to investigate the process of creating building that is environmentally friendly. It explores the aspects and standards that must be put in place in Malaysia's green construction sector. It also outlines the barriers to the green construction industry's adoption. This research also highlights the government entities that are working to maintain the green construction sector. This research focuses on Malaysia's green building system, referred to as the Green Building Index (GBI). A method scoring instrument lets developers and building owners to plan and construct environmentally friendly structures. Meanwhile, sustainable buildings may bring energy and water savings, a conducive indoor atmosphere, greater access to transportation, and the use of recycled materials and plants in their projects, all of which help decrease our environmental footprint. The qualitative technique, which is document or content analysis employed for this investigation. The research was based on interview and observation with multiple participants of the associated personnel, as well as the utilization of case studies from reference literature.